Child Second Language Development in Immersion Education A Study on Generic Determiner Phrases in L2 German and L2 French - Kolb, Nadine (Inquiries in Language Learning, 2022)
Language acquisition has been the subject of decades of research. Most of the previous research on second language acquisition has centered around adult learners, leaving child learners understudied by comparison. This book focuses on child second language development. The cross-sectional empirical study herein investigates the syntax-semantics interface in English speaking children acquiring German and French as second languages. The author discusses variables such as crosslinguistic influence, the complexity of the learning tasks, cognitive maturity and the learning context. By focusing on child second language acquisition in immersion education, this book not only substantially contributes to the field of second language acquisition but also offers important insights into teaching in an immersion context.